Perbedaan Kemampuan Pemecahan Masalah Matematika pada Setiap Rentang Usia - Muhammad 'Azmi Nuha; Ragil Meita Alfathy (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
Mathematics is a basic science which is about logic regarding form, structure, quantity and other related concepts. The ability to solve problems is basically the main goal of the mathematics learning process. The purpose of this study was to determine (1) whether there are differences in math problem solving abilities in each age range and (2) how to describe the ability to solve math problems in each age range. The method used in this research is quantitative research methods with a survey research approach. The instrument in this study was a questionnaire containing 3 mathematical problem solving questions related to everyday life which were uploaded to google form. The number of people who filled out the survey on the google form is 2085 people. The results showed that (1) there were differences in math problem solving abilities in each age range group, and (2) the age range group that had the highest problem solving ability was 43-48 years old, while the age range group that had the lowest problem solving ability was 43-48 years old. 55-60 years old.